Congenital pouch colon: A rare presentation of Anorectal malformation - Mahmood, Salah S.; Zain, Ahmed Z.; Aboalhab, Raghad J. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Congenital pouch colon is an usual abnormality associated with anorectal malformation in which the colon is partially or totally replaced by a pouch like dilatation connected to the genitourinary tract by a fistula(colovesical).The condition varies from complete absence of normal colon with the ileum opening into colonic pouch to the presence of nearly normal colon with only the rectum or recto sigmoid being attached to a pouch which in turn connected to bladder by a band or fistula. Objective: is to evaluate the methods of diagnosis and management of(C.P.C) with studying environmental factors especially pesticides and its prevalence. Patients and Methods: A total number of seven cases of(C.P.C) associated with high type of imperforate anus seen in Al-Emamain Al-Kadhemain Medical City and Al-Kadhemia Pediatric Hospital from October 2004 to October 2014. Results: Incidence of (C.P.C) was ( 2.9%) of all cases of high type of imperforate anus with male predominant ( 2.5:1).Most of patients were from Baghdad’s periphery with suspicioun of relationship of pesticides and its prevalence.Preoperative erect abdominal X-ray was diagnostic in (71%) especially type I and II .The most common type of (C.P.C)was type (II) (34%) followed by type (I) (28%). Abdomino-perineal pull-through and anoplasty were performed at mean age sixth month for most patients with resection or tabularizing of the pouch.Fecal continence was( 8o%) . Conclusions: Erect abdominal X-ray have to be done routinely for every case of high type ARM in order not to miss any case of (C.P.C).It is better to excise the pouch completely whatever type was because histopathological exam of the pouch revealed abnormal muscle coat with failure to produce propulsive movement.